Exploring the Interplay Between Cognitive Ability and Argumentation Skills to Improve Scientific Reasoning in Physics Learning - Dewi Kurniaty; Muslim Muslim; Hera Novia; Rizky Agassy Sihombing (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
This quantitative descriptive–correlational study explored the connection between senior high school students' cognitive abilities and their argumentation skills within the context of physics learning. Conducted at a public high school in Ketapang, West Kalimantan, the research utilized a multiple-choice test based on Bloom's revised taxonomy (C1–C5) to measure cognitive performance. Argumentation skills were evaluated using instruments aligned with Toulmin’s argument pattern (TAP). The findings revealed a decline in students' cognitive performance as task complexity increased, with scores of 78% for remembering, 61.25% for understanding, 45% for applying, 28.75% for analyzing, and 17.50% for evaluating. Similarly, argumentation skills showed a hierarchical pattern: 80% of students could state claims, 65.71% provided evidence, 51.43% explained phenomena, and only 34.29% were able to construct reasoned solutions. A Pearson correlation analysis indicated a strong, positive relationship between the two variables ( r>0.6;p<0.05). These results suggest that a higher level of cognitive ability is linked to stronger scientific argumentation, underscoring the necessity of integrating higher-order thinking skills into physics instruction to improve students' reasoning and scientific discourse.